A Study on Educational Philosophies Adopted by Teachers: The Case of Eskişehir - Turan Akman Erkılıç; İnci Zeynep Özonay Böcük (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
In this study, it is aimed to determine the educational philosophies adopted by the teachers working within the borders of Eskişehir on the basis of gender, branch, school type, and teaching experience. This study was carried out using the survey model, one of the quantitative research methods. Research data were obtained by reaching a total of 492 teachers in the 2020-2021 academic year. Scale of Educational Thought and Applications (ETA) developed by Kumral (2014) was used as the data collection tool. Data were analyzed through descriptive statistics, independent samples t test, paired samples t test and one-way analysis of variance (ANOVA). Results revealed that the teachers were closer to the contemporary educational philosophy. In the evaluations made according to the gender variable, it is seen that the traditional educational philosophy scores of the teachers differed significantly (p=.008), while the contemporary educational philosophy scores did not differ (p=1.151). According to the branch variable, it is seen that the scores of the teachers from both traditional (p=.070) and contemporary educational philosophy (p=.436) do not differ statistically. According to the school type variable, it was determined that there was a significant difference in teachers' traditional educational philosophy scores (p=.030), while there was no significant difference in contemporary educational philosophy scores (p=.424). When evaluated according to the teaching experience variable, it was found that there was a statistically significant difference in the traditional educational philosophy scores of the teachers (p=.014), while there was no significant difference in the contemporary educational philosophy scores (p=.061).